Implementasi Penghayatan Nilai Pancasila dan Kebinekaan dalam Menguatkan Identitas Manusia Indonesia di Sekolah Dasar - Tri Yudha Setiawan; Tresya Adila Putri; Stevie Yolanda; Putu Rita; Rangga Hasian Prakoso; Destrinelli Destrinelli; Muhammad Sofwan (Departement of Mathematics Education, 2024)
Education plays a central role in shaping the character and identity of a nation. In the context of Indonesia, the values of Pancasila and Bhinneka Tunggal Ika serve as philosophical foundations that guide the formation of a superior generation both academically and morally. This research aims to describe the implementation of the understanding of Pancasila values and diversity in strengthening the Indonesian identity at the Elementary School (SD) level. The method used is qualitative descriptive with data collection through observation, interviews, and documentation. The data validity test used in this research is technique triangulation. The results show that the implementation is carried out through learning activities, teacher role modeling, extracurricular activities, school culture, and Pancasila student profile strengthening projects. Through various activities, students can actively engage in understanding, internalizing, and implementing Pancasila values in their daily lives. Thus, the implementation of Pancasila values at the elementary school level can help strengthen the identity, unity, and integrity of the Indonesian nation through the formation of characters aligned with Pancasila values.